2000
DOI: 10.1159/000027084
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the Anal Canal and HIV Infection: Toxicity and Results of Organ Preservation with Radiochemotherapy or Radiotherapy

Abstract: Background: Anal cancer is an evolving problem in HIV-infected patients. In fear of excessive toxicity in patients with HIV infection, aggressive therapy is often withheld. Patients and Methods: From January 1995 to October 1997, 6 patients with epidermoid cancer of the anal canal and a long history of HIV infection but without symptoms of AIDS or repeated severe infections were treated with radiotherapy (1 patient) or radiochemotherapy (5 patients). External beam radiotherapy with 45 Gy to the tumor and pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Historically, prior to antiretroviral therapy (HAART), HIV-positive patients had clear worse prognosis and experienced worse toxicities from definitive chemoradiation (CRT) compared to immunocompetent patients (9,10). While HAART has increased the survival of patients with HIV (11,12), studies on treatment outcomes from CRT for SCCA according to HIV status have reported variables results in terms of recurrence and survival (2,(13)(14)(15). Therefore, we have undertaken a systematic review and meta-analyses about the efficacy and toxicity of CRT among patients with localized SCCA according to HIV status.…”
Section: Original Articlementioning
confidence: 99%
“…Historically, prior to antiretroviral therapy (HAART), HIV-positive patients had clear worse prognosis and experienced worse toxicities from definitive chemoradiation (CRT) compared to immunocompetent patients (9,10). While HAART has increased the survival of patients with HIV (11,12), studies on treatment outcomes from CRT for SCCA according to HIV status have reported variables results in terms of recurrence and survival (2,(13)(14)(15). Therefore, we have undertaken a systematic review and meta-analyses about the efficacy and toxicity of CRT among patients with localized SCCA according to HIV status.…”
Section: Original Articlementioning
confidence: 99%
“…During the past years, some reports were published which showed that treatment of anal cancer with a 5-FU/MMC containing radiochemotherapy is also feasible in patients with HIV infection [56,57], which seem to have a higher incidence for disease. HIV-positive patients tend to experience greater toxicity, especially when CD4 counts are below 200/μl.…”
Section: Anal Cancermentioning
confidence: 99%
“…Bei Patienten mit günstigen Prognosekriterien empfiehlt sich die bei der Behandlung des Analkarzinoms übliche Radio-/Chemotherapie mit Fluorouracil, Mitomycin und Bestrahlung. Hiermit lassen sich ähnliche Remissions-und Heilungsraten wie bei Nicht-HIV-Infizierten erreichen (Höcht et al 2000;Holland u. Swift 1994;Northfeldt 1996).…”
unclassified